2004
DOI: 10.4314/sajhe.v17i2.25309
|View full text |Cite
|
Sign up to set email alerts
|

Lecturers' experience of postgraduate supervision in a distance education context

Abstract: After determining the perceptions of postgraduate students at a distance education institution of the guidance they had experienced, a research project was launched to determine lecturers' views on supervision at the same institution. Data collection methods included focus groups, individual interviews and document analysis. Findings indicated that supervisors experienced some aspects of postgraduate supervision as extremely satisfying. However, numerous problems were raised, for example establishing acceptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 11 publications
4
28
0
Order By: Relevance
“…The study confirms the findings of other studies conducted elsewhere (Wang & Linda, 2008;Bitchener & Basturkmen, 2006;Lessing & Schulze, 2003), as pointed out in the literature review section of this article. This situation could be attributed to the following issues: First, given the trend of higher education students' enrolments in both undergraduate and postgraduate programs, this observation would not be surprising because the number of students pursuing postgraduate programs has increased tremendously in recent years.…”
Section: International Journal Of Research Studies In Education 79supporting
confidence: 81%
See 2 more Smart Citations
“…The study confirms the findings of other studies conducted elsewhere (Wang & Linda, 2008;Bitchener & Basturkmen, 2006;Lessing & Schulze, 2003), as pointed out in the literature review section of this article. This situation could be attributed to the following issues: First, given the trend of higher education students' enrolments in both undergraduate and postgraduate programs, this observation would not be surprising because the number of students pursuing postgraduate programs has increased tremendously in recent years.…”
Section: International Journal Of Research Studies In Education 79supporting
confidence: 81%
“…Most of the concerns have suggested that the quality of the research reports is low (Wang & Li, 2008;Bitchener & Basturkmen, 2006;Holbrook et al, 2004;Lessing & Schulze, 2003). In Tanzanian context, the review of external examination reports by the author of this article for theses and dissertations in four universities of Tanzania has revealed that one of the recurring comments by the examiners in the reports was on the candidates' weaknesses in presenting different chapters of the theses and dissertations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This statement re ects those of numerous postgraduate student participants who highlighted the need for more direction from their supervisors. Supervision is an important area and deserves further research and attention, as pointed out by LeGrange and Newmark (2002), Lessing and Schulze (2003), and Van der Westhuizen and De Wet (2002).…”
Section: Induction Into Pursuing Postgraduate Studiesmentioning
confidence: 97%
“…Subsequently, a number of studies have focused on the challenges related to potentially limiting success of postgraduate research students. Such studies have revealed that many postgraduate students drop out or fail to complete their studies within the stipulated time (Naim and Dhanapal 2015;Bitzer 2011;Herman 2011;Wadesango and Machingambi 2011;Dell 2010;Albertyn, Kapp and Bitzer 2008;Stack 2008;Abiddin 2007;Lessing and Schulze 2003).…”
Section: Introductionmentioning
confidence: 99%